Left femoral venous access for leadless pacemaker implantation: patient characteristics and outcomes. Issue 9 (5th April 2021) - Jelisejevas, Julius; Breitenstein, Alexander; Hofer, Daniel; Winnik, Stephan; Steffel, Jan; Saguner, Ardan M
Abstract: Aims: Leadless pacing has become an alternative approach for patients requiring a single-chamber pacemaker. Conventionally, leadless Micra Transcatheter Pacing System (TPS) pacemakers are implanted via a right femoral venous access. However, due to various reasons, a left-sided femoral venous approach may be necessary. We hypothesized that a left-sided femoral venous approach is as safe and effective when compared with a right-sided approach. We assessed indications, procedural characteristics, safety and mid-term outcomes of Micra TPS implantation via a left femoral venous approach when compared with the conventional right-sided approach. Methods and results: In this retrospective single-centre analysis, 143 consecutive patients undergoing Micra TPS implantation were included. 87% (125/143) underwent Micra TPS implantation via a right, and 13% (18/143) via a left femoral venous access. The mean age at implantation was 79.8 ± 7.5 years. Acute procedural success, mean procedure and fluoroscopy times as well as device parameters at implantation and follow-up (mean 15 ± 11.5 months) were similar between the two groups. Five major complications (3.5%) were encountered, all using a right-sided approach. After a transfemoral TAVI procedure, left femoral venous access was used in 42% of cases when compared with 8% in the remaining population ( P  = 0.003). Conclusions: A left femoral venous access for Micra TPS implantation is safe and effective with an excellent implantation success rate similar to a conventional right femoral venous access without longer implantation and fluoroscopy times. The most frequent reason for choosing left vs. right femoral venous access was a previous transfemoral TAVI procedure.